The archaeology of human bones - Mays, Simon (New York: Routledge, 2021)
"The Archaeology of Human Bones provides an up to date account of the analysis of human skeletal remains from archaeological sites, introducing students to the anatomy of bones and teeth and the nature of the burial record. Drawing from studies around the world, this book illustrates how the scientific study of human remains can provide answers to important archaeological and historical questions. This new edition reflects the latest developments in scientific techniques and their application to burial archaeology. Current scientific methods are explained, alongside a critical consideration of their strengths and weaknesses. The book has also been thoroughly revised to reflect changes in the ways in which scientific studies of human remains have influenced our understanding of the past, and has been updated to reflect developments in ethical debates that surround the treatment of human remains. There is now a separate chapter devoted to archaeological fieldwork on burial grounds, and the chapters on DNA and ethics have been completely rewritten. This edition of The Archaeology of Human Bones provides not only a more up to date but also a more comprehensive overview of this crucial area of archaeology. Written in a clear style with technical jargon kept to a minimum, it continues to be a key work for archaeology students"--
Includes bibliographical references and index.
Keywords: Anthropometry; Human remains (Archaeology); Paleopathology